2017
DOI: 10.5152/turkpediatriars.2017.2956
|View full text |Cite
|
Sign up to set email alerts
|

Plasmapheresis in a child with cold antibody autoimmune hemolytic anemia: case report

Abstract: Autoimmune hemolytic anemia is a picture of hemolysis which is caused by autoantibodies against red blood cell surface antigens. It is classified as primary, secondary or warm and cold autoimmune hemolytic anemia according to the temperature at which antibodies react. It is usually an acute and self-limiting condition. Here, we present a three-year-old male patient who presented with malaise, paleness, and dark-colored urine. His hemoglobin level was 5.8 g/dL, and increased indirect bilirubin and lactate dehyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…That is to say, there is at least 1 joint swelling and pain, there is evidence of arthritis (clinical or ultrasound or magnetic resonance imaging), arthritis caused by other diseases is excluded, and there is a typical routine RA radiological change or meet the RA classification criteria. According to the scoring system, a total score of 6 is diagnosed as RA [18,19], as shown in Table 1.…”
Section: Early Diagnosis Of Autoimmune Antibodiesmentioning
confidence: 99%
“…That is to say, there is at least 1 joint swelling and pain, there is evidence of arthritis (clinical or ultrasound or magnetic resonance imaging), arthritis caused by other diseases is excluded, and there is a typical routine RA radiological change or meet the RA classification criteria. According to the scoring system, a total score of 6 is diagnosed as RA [18,19], as shown in Table 1.…”
Section: Early Diagnosis Of Autoimmune Antibodiesmentioning
confidence: 99%
“…However, rather few data are available concerning the use of IVIG in CAD. A literature review revealed only one case of pediatric cold AIHA receiving IVIG, who was unresponsive to the treatment 5 . Although most published cases of AIHA received IVIG at a dose of 0.4‐0.5 mg/kg/day for five days, there is no consensus about optimal IVIG dosage.…”
Section: Figmentioning
confidence: 99%